1998
DOI: 10.1243/0309324981512904
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue properties of a glass-fibre-reinforced polyester material used in wind turbine blades

Abstract: Glass-fibre-reinforced polyester (GFRP) is a composite commonly used in the manufacture of wind turbine blades. In the present work, one such material has been subject to static and dynamic tests in order to obtain data that can be applied to the design of wind turbine blades and other machine elements. The results of the static tests established a basis for the determination of a set of tension-tension (constant amplitude and sinusoidal load) dynamic tests with the aim of establishing a mathematical model in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The classification societies' rules prescribe the procedure for obtaining S-N curves for composite materials. Various authors have reported results obtained in modeling S-N curves for composites [29,34,35] and the prediction of the fatigue life of composite structures [27,43,44]. A failure model for groups of similar glass/polyester composites, such as the ones used in this research, can be defined in the form:…”
Section: Structural Durability Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The classification societies' rules prescribe the procedure for obtaining S-N curves for composite materials. Various authors have reported results obtained in modeling S-N curves for composites [29,34,35] and the prediction of the fatigue life of composite structures [27,43,44]. A failure model for groups of similar glass/polyester composites, such as the ones used in this research, can be defined in the form:…”
Section: Structural Durability Assessmentmentioning
confidence: 99%
“…The fatigue of composites immersed in water has been investigated in the past [27,28]. Early research assumed that the absorbed moisture has no influence on the material fatigue strength in sinusoidal tension conditions, with a moisture content no greater than 0.2 percent [29]. However, newer research acknowledges the effects of water absorption on the fatigue strength of composites [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…If R is found to have no effect on GFRP life expectancy (Vázquez et al, 1998) and the effect of R on strain is confirmed, the conclusion would be that the failure point for a given σ max would be the same for different strain processes, 56 A. Silvera et al / Span J Agric Res (2011) 9(1), 49-58 4 Number of cycles at failure.…”
Section: Influence Of Stress Ratio Rmentioning
confidence: 99%
“…The moisture absorbed reduced ultimate tensile strength by 15% and fatigue strength by 35% (through 1,000 cycles) and 10% (through 10 7 cycles). Vázquez et al (1998) submerged samples in water at ambient temperature (24°C) for 45 days. The tests were conducted at laboratory temperature, i.e., 25°C.…”
Section: Influence Of the Cycle Of Ageing (Moistening/drying At Room mentioning
confidence: 99%
See 1 more Smart Citation